Spirituality for the skeptic - Solomon, Robert C. (Oxford University Press, 2007)
Spirituality for the Skeptic answers the need for a non-institutional, non-dogmatic spirituality that leads to personal fulfillment and satisfaction. By examing the ideas of the great thinkers from Socrates and Nietzche to Buddha and Kafka, Solomon arrives at a practical vision of spirituality that should appeal to many seekers looking to make sense of the human condition--Cover